Atributos microbiológicos e estoque de carbono e nitrogênio do solo com cobertura em áreas de cana-de-açúcar irrigada Jaíba-MG - Letícia Silva de Almeida (2015)
Brazil is the largest sugarcane producer in the world, one of the most important raw materials for the ethanol production, which puts the country in a privileged position in the global biofuels market. In recent years the cultivation of sugarcane has expanded into marginal areas with low soil fertility and water deficit problems. The use of irrigation is a revolution in the sugarcane production technology, since it increases the productivity and the longevity of sugarcane fields. In order to meet the national targets for ethanol production, consumption and export, planned for 2020, the sugarcane cultivation area should occupy approximately 19 million hectares. Soil management practices used in the sugarcane cultivation can influence the carbon and nutrient stocks. The maintenance of the sugarcane trash on the soil surface favors the biological processes responsible for soil nutrient cycling and maintaining the organic matter content. Thus, it becomes important to use soil bioindicators to assess and monitor the dynamics of soil carbon in irrigated sugarcane fields. Therefore, the objective of this study was to evaluate the effects of land use change into irrigated sugarcane crops in the dynamics of soil organic carbon, total nitrogen and microbiological attributes over time. Four cultivation areas were selected, named Cana 6, Cana 7, Cana 8, Cana 10 where the numbers represent the years of sugarcane cultivation , as well as a native vegetation (NV) area, localized next to the crops. Three composite samples of the soil were collected at 0-10, 10-20 and 20-30 cm deep in each study area. The samples were processed and analyzed for C and N stocks and the following biological properties: soil microbial biomass carbon (MBC); soil basal respiration (SBR), metabolic quotient (qCO2); and microbial quotient (qMIC). The Cana 8 system showed the highest values for MBC and the lowest values for qCO2, while the highest values for basal respiration and C and N stocks were observed in the NV. Such results are probably due to the continuous deposition of plant litter and to the NV biological activity. The implementation and renewal of irrigated sugarcane fields affect the functionality of soil biological processes. However, the maintenance of the sugarcane trash on the soil surface for long time contributed to the organic carbon use efficiency by soil microorganisms and to increase soil carbon and nitrogen stocks at levels similar to those found in areas of native vegetation.